The management of intra-abdominal infections from a global perspective: 2017 WSES guidelines for management of intra-abdominal infections - Sartelli, Massimo; Chichom-Mefire, Alain; Labricciosa, Francesco M; Hardcastle, Timothy; Abu-Zidan, Fikri M; Adesunkanmi, Abdulrashid K; Ansaloni, Luca; Bala, Miklosh; Balogh, Zsolt J; Beltrán, Marcelo A; Ben-Ishay, Offir; Biffl, Walter L; et al. (World journal of emergency surgery, 2017)
Intra-abdominal infections (IAIs) are common surgical emergencies and have been reported as major contributors to non-trauma deaths in the emergency departments worldwide. The cornerstones of effective treatment of IAIs are early recognition, adequate source control, and appropriate antimicrobial therapy. Prompt resuscitation of patients with ongoing sepsis is of utmost important. In hospitals worldwide, non-acceptance of, or lack of access to, accessible evidence-based practices and guidelines result in overall poorer outcome of patients suffering IAIs. The aim of this paper is to promote global standards of care in IAIs and update the 2013 WSES guidelines for management of intra-abdominal infections.
Keywords: Humans; Guidelines as Topic; Sepsis; směrnice jako téma; management nemoci; sepse; Intraabdominal Infections; lidé; antibakteriální látky; Abdominal Injuries; společnosti lékařské; nitrobřišní infekce; poranění břicha; vyhodnocení orgánové dysfunkce; chirurgové; Anti-Bacterial Agents; Intra-abdominal infections; peritonitida; Organ Dysfunction Scores; Surgeons; Societies, Medical; Peritonitis; Disease Management; Antibiotics